Enhancement of the microwave absorption properties of the SrFe12O19@Fe3O4@rGO composite material - Tran Thi Viet Nga; Nguyen Thi Lan; To Thanh Loan; Tran Quang Dat (Journal of Science: Advanced Materials and Devices, 2024)
In this work, graphene oxide (GO) was prepared via the Hummers’ method, whereas SrFe12O19, SrFe12O19@Fe3O4, and SrFe12O19@Fe3O4@rGO were fabricated using the hydrothermal techniques. The samples' phase structure, surface morphology, magnetic properties, and electromagnetic wave absorption characteristics were studied and compared. Findings show that the Fe3O4 particles adhered to the surface of the SrFe12O19 hexagonal plates, and the combination of SrFe12O19@Fe3O4 foam flakes and two-dimensional graphene rGO could enhance the absorption electromagnetic wave performance. The composite SrFe12O19@Fe3O4@rGO sample exhibited an ideal impedance matching within the frequency f range of 11 GHz–12.4 GHz. The minimum reflection loss reached −62.3 dB at 12.2 GHz with a thickness of 2 mm. With a thickness of 2 mm, the effective absorption bandwidth obtained the value of −20 dB, covering a range of 9.3 GHz. The composite SrFe12O19@Fe3O4@rGO sample, which shows the highest performance both in reflectivity and bandwidth, can find potential application in microwave absorptions.